An Analysis of Conflict Management through Islamic Organizational Communication in Islamic Educational Institutions - Hendri Purnama Sari; Ranita Ranita; Firda Fadila Ghassani; Arin Wibowo; Asmiranda Asmiranda; Kasinyo Harto; Febriyanti Febriyanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze conflict management based on Islamic organizational communication in Islamic educational institutions. Conflict is an inevitable phenomenon in organizations, including educational settings, where individuals with diverse backgrounds, interests, and perceptions interact. Therefore, effective conflict management strategies are required to ensure that conflicts do not produce negative impacts but instead contribute to organizational improvement. This research employs a qualitative approach using a case study method in an Islamic educational institution. Data were collected through in-depth interviews, observation, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques, with validity ensured through source and method triangulation. The findings reveal that conflicts occur among teachers, between teachers and leaders, and among staff, primarily caused by miscommunication, differences in interests, and varying perceptions. Organizational communication plays a strategic role in preventing and resolving conflicts through vertical, horizontal, and diagonal communication patterns, as well as communication strategies such as deliberation and interpersonal approaches. Furthermore, Islamic values such as consultation (shura), justice (‘adl), and reconciliation (ishlah) are proven to be effective in creating fair, humane, and sustainable conflict resolution. This study concludes that the integration of conflict management, organizational communication, and Islamic values can foster a harmonious and productive working environment. However, challenges remain, including communication barriers and inconsistency in applying Islamic values. Therefore, it is necessary to enhance organizational communication quality and strengthen the internalization of Islamic values in conflict management practices within Islamic educational institutions.